Digital filmmaking for beginners : a practical guide to video production - Hughes, Michael K. (New York [etc.] McGraw-Hill, 2012)
Digital video cameras are everywhere--even on our phones! But cameras don't make great movies; filmmakers do. Written by a seasoned pro with 40 years of teaching experience, Digital Filmmaking for Beginners is your fully illustrated introduction to all technical aspects of digital filmmaking. Featuring clear, concise instruction--accompanied by online video demonstrations--this comprehensive guide covers the best methods and techniques to plan and script projects; set up lighting, microphones, and cameras; and shoot, edit, and apply postproduction effects and other finishing touches. Whether you're an amateur film buff or an aspiring professional videographer, this is the source for everything you need to bring your ideas from the page to the screen.
Keywords: Vídeo digital -- Técnica; Cine -- Producción y dirección